Jennifer Capriati, teenage tennis star - Gutman, Bill. (Brookfield, Conn. : Millbrook Press, 1993)
Traces the tennis career of the young American player who made her professional debut at age thirteen.
Includes bibliographical references and index.
Keywords: Capriati, Jennifer -- Juvenile literature; Capriati, Jennifer; Tennis players -- United States -- Biography -- Juvenile literature; Tennis players; Women -- Biography